Mechanical analysis at different scales of gas pipelines. (August 2018) - Bolzon, Gabriella; Rivolta, Barbara; Nykyforchyn, Hryhoriy; Zvirko, Olha
Abstract: The actual safety margins of exercised gas pipelines depend on a number of factors that include the initial material properties and their evolution with time. These characteristics can be evaluated by mechanical tests of different complexity that can be performed on the pipeline steel at different scales. Alternative approaches based on traditional tensile tests and on instrumented indentation tests have been proposed and validated in some situations. The performances of these methodologies are compared in the present contribution for different pipe materials, in as-received and artificially aged conditions. Highlights: Different pipe materials are tested in as-received and artificially aged conditions. Different testing procedures are considered. The diagnostic capabilities of indentation tests performed at 200 N maximum load are assessed. The possibility of performing on-site experiments is envisaged.